2000
DOI: 10.1021/ja992680f
|View full text |Cite
|
Sign up to set email alerts
|

A Bis(μ-oxo)dicopper(III) Complex with Aromatic Nitrogen Donors:  Structural Characterization and Reversible Conversion between Copper(I) and Bis(μ-oxo)dicopper(III) Species

Abstract: Transformation of (µ-η 2 :η 2 -peroxo)dicopper(II) complexes bearing sterically bulky tridentate N,N′,N′′-trisubstituted tacn 2 to square pyramidal bis(µ-oxo)dicopper(III) complexes has been reported by Tolman et al. 3 In certain instances, they have observed a monooxygenase activity of the bis(µ-oxo)dicopper(III) complexes for the coordinated ligand as substrate. A different type of square planar bis(µ-oxo)dicopper(III) complexes having peralkylated-1,2-cyclohexanediamine ligands have been also prepared by S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
138
0
5

Year Published

2000
2000
2006
2006

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 138 publications
(157 citation statements)
references
References 16 publications
14
138
0
5
Order By: Relevance
“…+ (1), [2] as confirmed by the ESI-TOF mass spectrum. Compound 1 then reacts with further H 2 O 2 to give the selective formation of 4 (Supporting Information).…”
mentioning
confidence: 53%
See 3 more Smart Citations
“…+ (1), [2] as confirmed by the ESI-TOF mass spectrum. Compound 1 then reacts with further H 2 O 2 to give the selective formation of 4 (Supporting Information).…”
mentioning
confidence: 53%
“…[2] We also found that reaction of the bis(mhydroxo)dinickel(II) complex [Ni 2 (Me 2 -tpa) 2 (5) together with N-dealkylation of the Me 2 -tpa ligand. [3,4] A similar bis(m-alkylperoxo)dicopper(II) complex (6) has been reported by Tolman and co-workers in the reaction of the (m-h 2 :…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…[9] As mentioned already, the selective oxidation of the methyl group of Me 2 -tpa starts with the reaction of 1 with H 2 O 2 . To clarify the formation pathway of 4, we investigated the source of the oxygen in Me-tpa-CH 2 situation is in marked contrast to the formation of 5 and 6, where exogenous O 2 is the sole oxygen source. [3][4][5] A possible reactive species derived from the Me 2 -tpa ligand and some modified species derived from H 2 O 2 and O 2 is the ligand radical Me-tpa-CH 2 C, which has also been proposed for the formation of 5 and 6.…”
Section: }(Oor)]mentioning
confidence: 99%